Evaluation of seed and leaf epidermis characters in the taxonomy of some annual species of the genus Papaver (Papaveraceae). (12th May 2016) - Tavakkoli, Zahra; Assadi, Mostafa
Abstract : To get a better understanding of their taxonomic importance, we examined morphological, leaf epidermal and seed micromorphological characters of 19 taxa of annual Papaver L. belonging to the sections Papaver, Carinatae Fedde and Rhoeadium Spach. Among the studied taxa, the pattern of the coat of the seed testa cells and seed epidermal cell showed large variation. The granulate type of testa sculpturing was most common, but other types were represented by one or two species. In contrast, most of the taxa have broadly similar leaf epidermal characteristics. We conclude that variation in seed characters are significant for the taxonomy at the specific and generic levels, whereas leaf epidermis morphology, with few exceptions, is mostly only useful for separation of taxa within species. Based on the results, P. lacerum Popov is regarded as a synonym of P. commutatum Fisch. & C. A. Mey, while P. piptostigma Bienert ex Fedde, P. halophilum (Fedde) Cullen and P. tubuliferum Fedde are regarded as synonyms of P. macrostomum Boiss. et Huet ex Boiss. var. macrostomum . Further, Papaver gaubae Cullen & Rech. f. and P. bipinnatum C. A. Mey. are included into the synonymy list of P. glaucum Boiss. et Hausskn. and P. arenarium M.‐Bieb., respectively. In contrast, Papaver chelidoniifolium Fisch. & C. A. Mey. var. pinnatum Tavakkoli & Assadi from Gilan province is described as a new variety, and P. rhoeas L. var. strigosum Boenn. and var. glabrum Fedde and P. commutatum subsp. euxinum Kadereit are introduced as new records to Iran. The evolutionary and phylogenetic implications of the observed variation in seed characteristics are also discussed.